EFEKTIVITAS PEMBERIAN ZPT DAN KOMBINASI MEDIA PADA PERBANYAKAN TANAMAN LADA SECARA STEK - Nurul Istiqomah; Mahdiannoor Mahdiannoor; Norasiah Norasiah (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2017)
Cuttings play an important role in pepper plant seedling because it is more effective, efficient, and practical, and the resulting seeds have the same properties as the parent tree. Use of ZPT to spur the formation of rooting in cuttings. The composition of planting media has the ability to provide nutrients needed by plants to support the needs of live cuttings. This research aims to (i) to know the effectiveness of Rootone F interaction and media combination (ii) to know the effectiveness of Rootone F (iii) to know effectiveness of media combination (iv) to get the best dosage interaction effect of Rootone F and media combination (v) getting the best dosage Rootone F (vi) getting the best media combination on pepper plant propagation by cuttings. Using Factorial Random Block Design, the first factor is the dosage of Rootone F are f0 = 0 g.ℓ-1, f1 = 6 g.ℓ-1, f2 = 12 g.ℓ-1, f3 = 18 g.ℓ-1. The second factor is the combination of planting medium that is m0 = soil, m1 = soil + rice husk (2: 1), m2 = soil + chicken manure (2: 1), m3 = soil + rice husk + 2: 1: 1) with a combination of the two factors studied yielded 16 treatment combinations with three replicates as a group to obtain 48 experimental units. The experimental results showed that single factor of Rootone F had no effect while single factor of media combination and interaction between the two had an effect on shoot length and leaf number at 49 HST. The best treatment of media combination is m0 (soil) while the interaction of Rootone F and media combination is m0f2 (soil + dose 12 g.ℓ-1).